The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12864-020-6454-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of Clinopodium gracile (Benth.) Matsum and identification of genes related to Triterpenoid Saponin biosynthesis

Abstract: Background: Clinopodium gracile (Benth.) Matsum (C. gracile) is an annual herb with pharmacological properties effective in the treatment of various diseases, including hepatic carcinoma. Triterpenoid saponins are crucial bioactive compounds in C. gracile. However, the molecular understanding of the triterpenoid saponin biosynthesis pathway remains unclear. Results: In this study, we performed RNA sequencing (RNA-Seq) analysis of the flowers, leaves, roots, and stems of C. gracile plants using the BGISEQ-500 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…KEGG analysis of the up-regulated DEGs revealed that “terpenoid biosynthesis” was the highest among all pathways ( Figures 4C,D ), indicating that SA enhanced the expression of terpenoid metabolism in PTHRCs. Additionally, we noticed several DEGs were enriched in the biosynthesis pathway of other secondary metabolites, including phenylpropanoid, flavonoid and isoquinoline alkaloid ( Supplementary Table 3 ) consistent with Shan et al (2020) , suggesting SA might influence multiple processes of secondary metabolism in hairy roots.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…KEGG analysis of the up-regulated DEGs revealed that “terpenoid biosynthesis” was the highest among all pathways ( Figures 4C,D ), indicating that SA enhanced the expression of terpenoid metabolism in PTHRCs. Additionally, we noticed several DEGs were enriched in the biosynthesis pathway of other secondary metabolites, including phenylpropanoid, flavonoid and isoquinoline alkaloid ( Supplementary Table 3 ) consistent with Shan et al (2020) , suggesting SA might influence multiple processes of secondary metabolism in hairy roots.…”
Section: Discussionmentioning
confidence: 72%
“…Next-generation sequencing (e.g., Illumina RNA-seq) is an effective method to provide transcriptome-wide analysis of sequence data and differentially expressed genes (DEGs), especially for non-model plant species ( Ma et al, 2016 ; Choudhri et al, 2018 ). RNA-seq has been performed to identify the putative genes involved in terpenoid biosynthesis in multiple plants ( Luo et al, 2011 ; Ma et al, 2016 ; Wang et al, 2017 ; Zhou et al, 2017 ; Choudhri et al, 2018 ; Shan et al, 2020 ). Nevertheless, the short read lengths from RNA-seq restrict the construction of completely assembled transcripts, making it difficult to obtain full-length sequences ( Wu et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The identified four enzymes, SE, SHC, SS and DS, play important role in squalene biosynthesis and the subsequent catalytic reactions of this metabolic branch. The enzyme SS as a key enzyme in the terpenoid biosynthesis pathway catalyzes the synthesis of the first precursor of terpenoid compounds, squalene (Kim et al, 2005;Ye et al, 2014;Zheng et al, 2013;Dan et al, 2017;Shao et al, 2020). The SHC enzyme can catalyze the formation of hopene from its precursor squalene (Siedenburg and Jendrossek, 2011;Nakano et al, 2019), toward triterpenoid or steroid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The FL reads were corrected with RNA-seq reads using the LSC software [24]. Subsequently, the FL reads were clustered to generate de novo consensus isoforms via the iterative clustering for error correction algorithm and then polished using the Quiver quality-aware algorithm [49]. Two strategies were employed to improve the accuracy of consensus transcripts.…”
Section: Iso-seq Data Processingmentioning
confidence: 99%